Nurses Knowledge and Performance Toward Physical Restraint at Critical Care Units - Hamid, Abbas; Hattab, Wafaa Abed Ali (Iraqi National Journal of Nursing Specialties, 2023)
Abstract: Objective: The study was done to evaluate nurses’ knowledge and practices toward physical restraint at critical care unit Methodology: Fifty nurses, who were selected by a non-probability (convenient) sampling method, participated in this descriptive study. The instrument of the study was knowledge parts of the questionnaire were initially developed in the U.S.A for nursing homes; in 2006 they were adopted for all hospital units by the original developers. The knowledge section of the questionnaire consisted of 20 items, which were used to measure knowledge of nurses towards the definition, indications and contraindications, proper application and legal and ethical considerations of physical restraint use. A three- point ordinal scale (Agree, Uncertain and Disagree) was applied to determine nurses’ responses to the items; it contained negative and positive sentences. Positive items, if answered with “agree,” were considered correct; if answered with “disagree,” items were considered incorrect. To evaluate the nurse’s practices with respect to physical restraint, the researcher observes and checks for correct or incorrect performance. The practices checklist for nurses is composed of (94) items divided into six content domains. Results: The result of this research showed that 90% of nurses had low knowledge about physical restraint, and 80 % of the participants had unsatisfactory performance. Recommendation: The study recommended development of local policies for physical restraint use including detailed descriptions of conditions requiring its use is mandatory. Key words- Knowledge, Performance, Physical Restraint, Critical Care Units